Analysis of the Cooperation Agreement between the Health Social Security Administering Agency (BPJS) and Hospitals on Determining Postponed Claims at the Datu Beru Takengon Regional General Hospital, Central Aceh - Cipta Burnama, Eko; Sumarno , Sumarno; Dahlan, Dahlan (Jurnal Ekonomi, 2024)
This study examines the Cooperation Agreement between the the Social Security Provider (BPJS) for Health and Hospitals and how it impacts the delay in claim payments at RSUD Datu Beru Takengon in 2023. The research employs a juridicalempirical method focusing on the analysis of the Cooperation Agreement documents. The findings reveal that coding discrepancies are the major cause of claim delays, with a total of Rp 4,370,529,800 in delayed claims throughout 2023. While the cooperation agreement outlines rights and obligations for both parties, it lacks specific attention to resolving delayed claims. Therefore, the agreement needs improvement by emphasizing the prevention of claim delay cases to avoid negative impacts on hospitals and healthcare services.